Placental site trophoblastic tumor: report of successful management with combination chemotherapy, subsequent spontaneous conception, and a live birth at term - Clement Adepiti; Akaninyene Ubom; Ibraheem Awowole; Kayode Ajenifuja (Reviews in Clinical Medicine)
Introduction: Placental site trophoblastic tumor (PSTT) is a rare form of gestational trophoblastic disease (GTD) that is usually associated with high mortality compared to the other subtypes because of its unpredictable biological behavior, less responsiveness to chemotherapy, and poor prognosis. Case Presentation: We present a 27year old nulliparous lady referred to our centre for recurrent vaginal bleeding following two evacuations for an incomplete spontaneous miscarriage after eight weeks of amenorrhea. Her assessment revealed low serum beta-human chorionic gonadotropin (βhCG) and high human placental lactogen (hPL) levels. Ultrasound scan and Doppler study showed a highly vascular tumor infiltrating the myometrium. She strongly desired to preserve her fertility and was initially commenced on low dose Methotrexate with marginal reduction in tumor volume and resistance on higher dose. She responded well to combination chemotherapy and the tumor disappeared after the second course. She received three additional courses and was followed up with serial ultrasonography for one year. She subsequently conceived spontaneously, with vaginal delivery of a live, normal female baby at term. Conclusion: Though hysterectomy combined with chemotherapy is the recommended management for PSTT and serum hPL is the usual tumor marker for follow-up, we present a case of successful treatment with combination chemotherapy alone and follow-up with subsequent cure, spontaneous conception, and delivery of a live baby.